GEOKIMIA BATUAN VOLKANIK FORMASI CIKOTOK DI SEGMEN UTARA KUBAH BAYAH, BANTEN - Hutabarat, Johanes (Bulletin of Scientific Contribution, 2016)
The Bayah Dome area compiled by various rock formations either volcanic rock and also sediment, where the volcanic rock is in general is main compiler from Cikotok and Cimapag Formation which age Tersier. Volcanic rock in Bayah Dome is distinguishable to become two main lithology types that are coherent- and non-coherent volcanic roks. Coherent volcanic roks in  Bayah dome northern segmentconsist of basalt-, and andesitelava. Andesitic lava is dominant rock. Both types of the lithology in general has experienced hydrothermal alteration distinguished with there is of secondary mineral like chlorite, sericite, carbonate, clay and opaq minerals. The mineralogical and rock geochemistry composition, the volcanic rock has been formed in island arc environment characterized by content SiO2 is ranging from 48.29%-58.34%, Al2O3 between 12.49%-17.18%; TiO2 and P2O5 ranges from 0.49%-0.81%, and 0.20%-0.41% respectively. Keywords: Andesite, Basalt, Hydrothermal alteration, Volkanic Calk-alkaline, Island arc.Daerah Kubah Bayah disusun oleh berbagai formasi batuan baik batuan volkanik maupun sedimen, dimana batuan volkaniknya  pada umumnya merupakan penyusun utama dari Formasi Cikotok dan Cimapag yang berumur Tersier. Batuan volkanik di Kubah Bayah dapat di bedakan menjadi dua jenis litologi yang utama yaitu batuan volkanik koheren dan batuan volkanik non-koheren. Batuan volkanik koheren di segemen utara Kubah Bayah terdiri dari lava basalt, dan andesit.  Andesitik merupakan batuan yang dominan. Kedua jenis litologi tersebut  pada umumnya telah mengalami ubahan hidrotermal yang dicirikan dengan terdapatnya mineral sekunder seperti klorit, serisit, karbonat, mineral lempung,  dan  mineral opak. Secara komposisi mineralogi dan geokimia batuan, batuan volkanik tersebut terbentuk di lingkungan busur kepulauan yang ditandai oleh kandungan kandungan SiO2 yang berkisar antara 48.29%-58.34%, Al2O3 antara 12.49%-17.18%; TiO2 dan P2O5 berturutan berkisar antara 0.49%-0.81%, dan 0.20%-0.41%. Kata Kunci: Andesit, Basalt, Alterasi hidrotermal, Volkanik Kalk-alkali, Busur Kepulauan.